Analysis of second-generation epigenetic clocks reveals further associations between disproportionate biological ageing and hippocampal volume - Lidija Milicic; Michael Vacher; Vincent Doré; Pierrick Bourgeat; Rosita Shishegar; James D. Doecke; Paul Maruff; Christopher C. Rowe; Victor L. Villemagne; Michael Weiner; Paul Aisen; Ronald Petersen; et al. (GeroScience, 2026)

Global analysis reveals persistent shortfalls and regional differences in availability of foods needed for health - Leah Costlow; Anna Herforth; Timothy B. Sulser; Nicola Cenacchi; William A. Masters (Global Food Security, 2025)

Association of Sport Helmet Status on Concussion Presentation and Recovery in Male Collegiate Student-Athletes - Adrian J. Boltz; Landon B. Lempke; Reid A. Syrydiuk; Stefan Duma; Paul Pasquina; Thomas W. McAllister; Michael McCrea; Avinash Chandran; Steven P. Broglio; Louise Kelly; Justus Ortega; Nicholas Port; et al. (Annals of Biomedical Engineering, 2024)

Head Impact Kinematics and Brain Tissue Strains in High School Lacrosse - Declan A. Patton; Colin M. Huber; Divya Jain; Svein Kleiven; Zhou Zhou; Christina L. Master; Kristy B. Arbogast (Annals of Biomedical Engineering, 2024)

Female Collegiate Athletes’ Concussion Characteristics and Recovery Patterns: A Report from the NCAA-DoD CARE Consortium - Landon B. Lempke; Jaclyn B. Caccese; Reid A. Syrydiuk; Thomas A. Buckley; Sara P. D. Chrisman; James R. Clugston; James T. Eckner; Elsa Ermer; Carrie Esopenko; Divya Jain; Louise A. Kelly; Allyssa K. Memmini; et al. (Annals of Biomedical Engineering, 2024)

Initial Mild Traumatic Brain Injury Characteristics and Recovery Patterns Among Females Across the United States Military Service Academies: A Report from the NCAA-DoD CARE Consortium - Landon B. Lempke; Elsa Ermer; Adrian J. Boltz; Jaclyn Caccese; Thomas A. Buckley; Kenneth L. Cameron; Sara P. D. Chrisman; Christopher D’Lauro; James T. Eckner; Carrie Esopenko; Tamerah N. Hunt; Divya Jain; et al. (Annals of Biomedical Engineering, 2024)

Africa Alive Corridors: Transdisciplinary Research based on African Footprints - B. Linol; M. Doucouré; J. Anderson; F. Toteu; W. Miller; P. Vale; P. Hoffman; G. I. H. Kerley; R. Auerbach; C. Thiart; M. Meghraoui; N. Dhliwayo; et al. (Geoheritage, 2024)
The idea of Africa Alive Corridors (AAC) evolved from Gondwana geological mapping to a comprehensive, more inclusive and dynamic approach to transdisciplinary research known as Earth Stewardship Science. Twenty designated corridors explore the geo-biological and cultural heritage of different regions of Africa over various periods, from deep time to the Anthropocene. Each corridor reveals a specific lens through which to investigate some of the rich scientific narratives embedded within it. The concept also facilitates learning and knowledge exchange across numerous disciplines: archeology, geology, geophysics, oceanography, glaciology, biology, botany, ecology, agriculture, engineering, spatial statistics, social sciences, and the humanities. This contribution analyses ten selected corridors in southern and western Africa, the Congo Basin, East Africa, and Madagascar. The various research themes explored include Earth impact hazard, origins of humankind, Snowball Earth, coastal food systems and conservation, the biogeography of lemurs, human settlement dynamics in Cameroon, tectonically linked earthquake occurrences in Algeria and Morocco, modelling land-use changes in the Western Rift Valley, trades and civilizations of the Mali Empire, Mbira music, and contemporary art. The ongoing work on these—and ten other—corridors has considerable potential to host new international collaborations to develop the links between society and natural sciences in Africa. Ultimately, AAC will benefit all stakeholders, especially the youth, in understanding and responding to societal needs and current global challenges.

Upscaling marine forest restoration: challenges, solutions and recommendations from the Green Gravel Action Group - Georgina Valentine Wood; Karen Filbee-Dexter; Melinda Ann Coleman; Jurgen Valckenaere; J. David Aguirre; Paige M. Bentley; Paul Carnell; Phoebe Damayanthi Dawkins; Lauren N. Dykman; Hannah S. Earp; Leeann B. Ennis; Prue Francis; et al. (Frontiers in Marine Science, 2024)
Introduction To counteract the rapid loss of marine forests globally and meet international commitments of the UN Decade on Ecosystem Restoration and the Convention on Biological Diversity ‘30 by 30’ targets, there is an urgent need to enhance our capacity for macroalgal restoration. The Green Gravel Action Group (GGAG) is a global network of 67 members that are working on the restoration of a diverse range of macroalgal forests and it aims to facilitate knowledge exchange to fast-track innovation and implementation of outplanting approaches worldwide. Methods Here, we overview 25 projects conducted by members of the group that are focused on testing and developing techniques for macroalgal restoration. Based on these projects, we summarise the major challenges associated with scaling up the area of marine forests restored. Results We identify several critical challenges that currently impede more widespread rollout of effective large-scale macroalgal restoration worldwide: 1) funding and capacity limitations, 2) difficulties arising from conditions at restoration sites, 3) technical barriers, and 4) challenges at the restoration-policy interface. Discussion Despite these challenges, there has been substantial progress, with an increasing number of efforts, community engagement and momentum towards scaling up activities in recent years. Drawing on the collective expertise of the GGAG, we outline key recommendations for the scaling up of restoration efforts to match the goals of international commitments. These include the establishment of novel pathways to fund macroalgal restoration activities, building skills and capacity, harnessing emerging innovations in mobile hatchery and seeding technologies, and the development of the scientific and governance frameworks necessary to implement and monitor macroalgal restoration projects at scale.

Direct and indirect effects of Basta®, a glufosinate-based herbicide, on banana plantation soil microbial diversity and function - Anthony B. Pattison; Anna V. McBeath; Bronwyn Masters; Paul G. Dennis (Applied Soil Ecology, 2024)

Validating assumptions in calculating carbon dioxide removal by enhanced rock weathering in Kantola et al., 2023 - Adam Wolf; Elliot Chang; Ilsa B. Kantola; Elena Blanc‐Betes; Michael D. Masters; Alison Marklein; Caitlin E. Moore; Carl J. Bernacchi; Evan H. DeLucia (Global Change Biology, 2024)

Improved net carbon budgets in the US Midwest through direct measured impacts of enhanced weathering - Ilsa B. Kantola; Elena Blanc‐Betes; Michael D. Masters; Elliot Chang; Alison Marklein; Caitlin E. Moore; Adam von Haden; Carl J. Bernacchi; Adam Wolf; Dimitar Z. Epihov; David J. Beerling; Evan H. DeLucia (Global Change Biology, 2023)
Terrestrial enhanced weathering (EW) through the application of Mg‐ or Ca‐rich rock dust to soil is a negative emission technology with the potential to address impacts of climate change. The effectiveness of EW was tested over 4 years by spreading ground basalt (50 t ha −1 year −1 ) on maize/soybean and miscanthus cropping systems in the Midwest US. The major elements of the carbon budget were quantified through measurements of eddy covariance, soil carbon flux, and biomass. The movement of Mg and Ca to deep soil, released by weathering, balanced by a corresponding alkalinity flux, was used to measure the drawdown of CO 2 , where the release of cations from basalt was measured as the ratio of rare earth elements to base cations in the applied rock dust and in the surface soil. Basalt application stimulated peak biomass and net primary production in both cropping systems and caused a small but significant stimulation of soil respiration. Net ecosystem carbon balance (NECB) was strongly negative for maize/soybean (−199 to −453 g C m −2 year −1 ) indicating this system was losing carbon to the atmosphere. Average EW (102 g C m −2 year −1 ) offset carbon loss in the maize/soybean by 23%–42%. NECB of miscanthus was positive (63–129 g C m −2 year −1 ), indicating carbon gain in the system, and EW greatly increased inorganic carbon storage by an additional 234 g C m −2 year −1 . Our analysis indicates a co‐deployment of a perennial biofuel crop (miscanthus) with EW leads to major wins—increased harvested yields of 29%–42% with additional carbon dioxide removal (CDR) of 8.6 t CO 2 ha −1 year −1 . EW applied to maize/soybean drives a CDR of 3.7 t CO 2 ha −1 year −1 , which partially offsets well‐established carbon losses from soil from this crop rotation. EW applied in the US Midwest creates measurable improvements to the carbon budgets perennial bioenergy crops and conventional row crops.

Economic returns and the perceived obstacles to adopting active management in the forest-grassland transition ecoregion in south-central USA - Bijesh Mishra; Omkar Joshi; Ronald E. Masters; Caleb McKinney; Arjun Adhikari; Chris B. Zou; Rodney E. Will (Journal of Environmental Management, 2023)

Forage quantity and protein concentration changes across a forest-savanna gradient with management implications for white-tailed deer - Caleb M. McKinney; Ronald E. Masters; Arjun Adhikari; Bijesh Mishra; Omkar Joshi; Chris B. Zou; Rodney E. Will (Forest Ecology and Management, 2023)

Comprehensive analysis of epigenetic clocks reveals associations between disproportionate biological ageing and hippocampal volume - Lidija Milicic; Michael Vacher; Tenielle Porter; Vincent Doré; Samantha C. Burnham; Pierrick Bourgeat; Rosita Shishegar; James Doecke; Nicola J. Armstrong; Rick Tankard; Paul Maruff; Colin L. Masters; et al. (GeroScience, 2022)
The concept of age acceleration, the difference between biological age and chronological age, is of growing interest, particularly with respect to age-related disorders, such as Alzheimer’s Disease (AD). Whilst studies have reported associations with AD risk and related phenotypes, there remains a lack of consensus on these associations. Here we aimed to comprehensively investigate the relationship between five recognised measures of age acceleration, based on DNA methylation patterns (DNAm age), and cross-sectional and longitudinal cognition and AD-related neuroimaging phenotypes (volumetric MRI and Amyloid-β PET) in the Australian Imaging, Biomarkers and Lifestyle (AIBL) and the Alzheimer’s Disease Neuroimaging Initiative (ADNI). Significant associations were observed between age acceleration using the Hannum epigenetic clock and cross-sectional hippocampal volume in AIBL and replicated in ADNI. In AIBL, several other findings were observed cross-sectionally, including a significant association between hippocampal volume and the Hannum and Phenoage epigenetic clocks. Further, significant associations were also observed between hippocampal volume and the Zhang and Phenoage epigenetic clocks within Amyloid-β positive individuals. However, these were not validated within the ADNI cohort. No associations between age acceleration and other Alzheimer’s disease-related phenotypes, including measures of cognition or brain Amyloid-β burden, were observed, and there was no association with longitudinal change in any phenotype. This study presents a link between age acceleration, as determined using DNA methylation, and hippocampal volume that was statistically significant across two highly characterised cohorts. The results presented in this study contribute to a growing literature that supports the role of epigenetic modifications in ageing and AD-related phenotypes.

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Head Impact Sensor Studies In Sports: A Systematic Review Of Exposure Confirmation Methods - Declan A. Patton; Colin M. Huber; Divya Jain; Rachel K. Myers; Catherine C. McDonald; Susan S. Margulies; Christina L. Master; Kristy B. Arbogast (Annals of Biomedical Engineering, 2020)

Quantitative Microbial Risk Assessment and Infectious Disease Transmission Modeling of Waterborne Enteric Pathogens - Andrew F. Brouwer; Nina B. Masters; Joseph N. S. Eisenberg (Current Environmental Health Reports, 2018)

Invasion and translocation of uropathogenic Escherichia coli isolated from urosepsis and patients with community-acquired urinary tract infection - B. Owrangi; N. Masters; A. Kuballa; C. O’Dea; T. L. Vollmerhausen; M. Katouli (European Journal of Clinical Microbiology & Infectious Diseases, 2018)

A continental‐scale analysis of feral cat diet in Australia - Tim S. Doherty; Robert A. Davis; Eddie J. B. van Etten; Dave Algar; Neil Collier; Chris R. Dickman; Glenn Edwards; Pip Masters; Russell Palmer; Sue Robinson (Journal of Biogeography, 2015)
Aim Reducing the impacts of feral cats ( Felis catus ) is a priority for conservation managers across the globe, and success in achieving this aim requires a detailed understanding of the species’ ecology across a broad spectrum of climatic and environmental conditions. We reviewed the diet of the feral cat across Australia and on Australian territorial islands, seeking to identify biogeographical patterns in dietary composition and diversity, and use the results to consider how feral cats may best be managed. Location Australia and its territorial islands. Methods Using 49 published and unpublished data sets, we modelled trophic diversity and the consumption of eight food groups against latitude, longitude, mean temperature, precipitation, environmental productivity and climate‐habitat regions. Results We recorded 400 vertebrate species that feral cats feed on or kill in Australia, including 28 IUCN Red List species. We found evidence of continental‐scale prey‐switching from rabbits to small mammals, previously recorded only at the local scale. The consumption of arthropods, reptiles, rabbits, rodents and medium‐sized native mammals varied with different combinations of latitude, longitude, mean annual precipitation, temperature and environmental productivity. The frequency of rodents and dasyurids in cats’ diets increased as rabbit consumption decreased. Main conclusions The feral cat is an opportunistic, generalist carnivore that consumes a diverse suite of vertebrate prey across Australia. It uses a facultative feeding strategy, feeding mainly on rabbits when they are available, but switching to other food groups when they are not. Control programmes aimed at culling rabbits could potentially decrease the availability of a preferred food source for cats and then lead to greater predation pressure on native mammals. The interplay between cat diet and prey species diversity at a continental scale is complex, and thus cat management is likely to be necessary and most effective at the local landscape level.

Prevalence of β-thalassemia and other haemoglobinopathies in six cities in India: a multicentre study - D. Mohanty; R. B. Colah; A. C. Gorakshakar; R. Z. Patel; D. C. Master; J. Mahanta; S. K. Sharma; U. Chaudhari; M. Ghosh; S. Das; R. P. Britt; S. Singh; et al. (Journal of Community Genetics, 2013)

Comparison of Global Mean Sea Level Time Series from TOPEX/Poseidon, Jason-1, and Jason-2 - D. Masters; R. S. Nerem; C. Choe; E. Leuliette; B. Beckley; N. White; M. Ablain (Marine Geodesy, 2012)

Herbicides for Establishing Switchgrass in the Central and Northern Great Plains - Robert B. Mitchell; Kenneth P. Vogel; John Berdahl; Robert A. Masters (BioEnergy Research, 2010)

The structure of dopamine induced α-synuclein oligomers - Agata Rekas; Robert B. Knott; Anna Sokolova; Kevin J. Barnham; Keyla A. Perez; Colin L. Masters; Simon C. Drew; Roberto Cappai; Cyril C. Curtain; Chi L. L. Pham (European Biophysics Journal, 2010)

ORIGINAL ARTICLE: Eyes wide shut: can hypometabolism really explain the primate colonization of Madagascar? - J. C. Masters; B. G. Lovegrove; M. J. De Wit (Journal of Biogeography, 2007)
Aim We investigate the hypothesis that it was the capacity for torpor or hibernation that enabled the lemuriforms (and possibly other mammal groups, e.g. tenrecs and rodents) to invade Madagascar by means of over‐water dispersal. Location Madagascar, East Africa and the Mozambique Channel. Methods We consider the body weights and life‐style features of living primate taxa that employ heterothermy. Using this information as a standard for comparison, we summarize the available information on the Palaeogene strepsirrhine radiation (i.e. members of the infraorder Adapiformes, the extinct sister‐taxon to the lemuriforms, as well as putative stem lemuriforms), particularly with respect to possible trends in body weight among early, middle and late Eocene adapiforms. We discuss Eocene climatic conditions in the northern hemisphere and Africa, and assess the likelihood of adaptations for heterothermy in adapiforms. Finally, we estimate the body weights of the common ancestors to the living Lemuriformes and Lemuroidea using the method of phylogenetically independent contrasts. Results The mean body weights estimated for the early, middle and late Eocene strepsirrhine faunas remain at approximately 2 kg, outside of the range of living primates using heterothermy. The adapiforms’ appearance coincided with the ‘initial Eocene thermal maximum’, an unusually hot period of global warming, and their demise corresponded with a major cooling event coincident with the appearance of ice sheets on Antarctica. They show no evidence of having evolved adaptations that allowed them to withstand climatic deterioration. The body weights of the ancestral lemuriform and ancestral lemuroid are of a similar order to the mean body weight estimated for the adapiforms, i.e. approximately 1.8 and 2.1 kg, respectively. Main conclusions The available evidence argues against the widespread use of heterothermy by adapiforms. The adapiform–lemuriform divergence may have been the result of the lemuriforms adapting to the drier and more seasonal environments that characterized the African Eocene, and this suite of adaptations may have included the use of heterothermy, but there is as yet no substantial evidence to confirm the presence of either group on the continent prior to c. 40 Ma. The estimated body weights of the common lemuriform and lemuroid ancestors are well outside the size range of living mammals that employ heterothermy. We conclude that the hypothesis that it was the ability to use heterothermy that enabled the strepsirrhines, and not the haplorhines, to invade Madagascar, is unlikely. Alternative explanations for this anomaly should be sought.

Copper Modulation of Ion Channels of PrP[106–126] Mutant Prion Peptide Fragments - J. I. Kourie; B. L. Kenna; D. Tew; M. F. Jobling; C. C. Curtain; C. L. Masters; K. J. Barnham; R. Cappai (The Journal of Membrane Biology, 2003)

A simple activity monitoring radio tag for fish - W. R. C. Beaumont; B. Cresswell; K. H. Hodder; J. E. G. Masters; J. S. Welton (Hydrobiologia, 2002)

Herbivory in global climate change research: direct effects of rising temperature on insect herbivores - Jeffery S. Bale; Gregory J. Masters; Ian D. Hodkinson; Caroline Awmack; T. Martijn Bezemer; Valerie K. Brown; Jennifer Butterfield; Alan Buse; John C. Coulson; John Farrar; John E. G. Good; Richard Harrington; et al. (Global Change Biology, 2002)
This review examines the direct effects of climate change on insect herbivores. Temperature is identified as the dominant abiotic factor directly affecting herbivorous insects. There is little evidence of any direct effects of CO 2 or UVB. Direct impacts of precipitation have been largely neglected in current research on climate change. Temperature directly affects development, survival, range and abundance. Species with a large geographical range will tend to be less affected. The main effect of temperature in temperate regions is to influence winter survival; at more northerly latitudes, higher temperatures extend the summer season, increasing the available thermal budget for growth and reproduction. Photoperiod is the dominant cue for the seasonal synchrony of temperate insects, but their thermal requirements may differ at different times of year. Interactions between photoperiod and temperature determine phenology; the two factors do not necessarily operate in tandem. Insect herbivores show a number of distinct life‐history strategies to exploit plants with different growth forms and strategies, which will be differentially affected by climate warming. There are still many challenges facing biologists in predicting and monitoring the impacts of climate change. Future research needs to consider insect herbivore phenotypic and genotypic flexibility, their responses to global change parameters operating in concert, and awareness that some patterns may only become apparent in the longer term.

Liposphere Local Anesthetic Timed-Release for Perineural Site Application - David B. Masters; Abraham J. Domb (Pharmaceutical Research, 1998)

Relationships between NADPH diaphorase staining and neuronal, endothelial, and inducible nitric oxide synthase and cytochrome P450 reductase immunoreactivities in guinea-pig tissues - H. M. Young; Anna J. O'Brien; John B. Furness; Daniela Ciampoli; James P. Hardwick; Timothy J. McCabe; Ramani Narayanasami; Bettie Sue S. Masters; W. Ross Tracey (Histochemistry and Cell Biology, 1997)